EDUKASI PERILAKU HIDUP SEHAT DAN BERSIH (PHBS) SERTA CARA PENCEGAHAN PENYEBARAN COVID-19 PADA MASYARAKAT NUNUK KEC. PINOLOSIAN, SULAWESI UTARA - Adnan Malaha; Nur Fauzia; Novarita (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Health is a condition where a person feels fine, which is emphasized by the results of supporting examinations that state normal conditions. Action in implementing clean and healthy living behavior (PHBS) is also a form of prevention in keeping the body healthy. PHBS is the practice of a collection of behaviors based on awareness as a result of individual and community group learning in maintaining their health so as to prevent Covid-19 transmission and improve public health status.